(untitled) (Proximus Journal of Sports Science and Physical Education, 2026)
The article examines the theoretical and practical aspects of applying a systems approach in the teaching of physical education. It reveals the essence of the systems approach as a methodological foundation of pedagogical activity and analyzes the structural components of the pedagogical system and their interrelations. Special attention is given to the practical implementation of the systems approach in physical education classes, including the development of motor skills, the enhancement of physical qualities, and the motivation of students. The provided examples demonstrate the effectiveness of a systematically organized learning process. It is concluded that the systems approach contributes to improving the quality of education, fostering students’ personal development, and optimizing the educational process.